1994
DOI: 10.1016/0735-1097(94)90740-4
|View full text |Cite
|
Sign up to set email alerts
|

The causes of dilated cardiomyopathy: A clinicopathologic review of 673 consecutive patients

Abstract: Idiopathic dilated cardiomyopathy is a common cause of congestive heart failure. Specific heart muscle diseases occur with much less frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0
18

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(131 citation statements)
references
References 44 publications
5
108
0
18
Order By: Relevance
“…O conhecimento das alterações do aparelho valvar mitral tem aplicabilidade direta no aprimoramento das diversas técnicas de correção cirúrgica que intervêm sobre o anel, as cúspides, as cordas tendíneas e os músculos papilares, em associações ou isoladamente, justificando seu estudo anatômico na cardiomiopatia dilatada (9,10) . O GRUPO II com 20 corações de cadáveres humanos, fixados, oriundos de cadáveres sem cardiopatia prévia cuja "causa mortis" foi o trauma.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…O conhecimento das alterações do aparelho valvar mitral tem aplicabilidade direta no aprimoramento das diversas técnicas de correção cirúrgica que intervêm sobre o anel, as cúspides, as cordas tendíneas e os músculos papilares, em associações ou isoladamente, justificando seu estudo anatômico na cardiomiopatia dilatada (9,10) . O GRUPO II com 20 corações de cadáveres humanos, fixados, oriundos de cadáveres sem cardiopatia prévia cuja "causa mortis" foi o trauma.…”
Section: Introductionunclassified
“…O GRUPO II com 20 corações de cadáveres humanos, fixados, oriundos de cadáveres sem cardiopatia prévia cuja "causa mortis" foi o trauma. Para caracterizar os corações com CMD utilizaramse critérios (10,11) :…”
Section: Introductionunclassified
“…The prevalence has not been clearly determined, but a study involving a series of 673 patients with dilated cardiomyopathy found that only 1 case of AF was caused by tachycardia. 59 Atrial fibrillation may not only cause the cardiomyopathy but may also exacerbate the symptoms of heart failure as a result of diastolic filling abnormalities and tachycardia-induced systolic dysfunction. Various cellular mechanisms have been implicated as causes of tachycardia-mediated cardiomyopathy, including the depletion of myocardial energy stores by chronic tachycardia, which causes oxidative stress and injury and leads to abnormal calcium handling and β-adrenergic responsiveness.…”
Section: Tachycardia-mediated Cardiomyopathymentioning
confidence: 99%
“…Specific mutations in the LMNA gene can result in isolated cardiac involvement in which the affected individuals develop dilated cardiomyopathy with or without conduction system disease. Dilated cardiomyopathy is a disorder of the myocyte characterized by cardiac dilation and systolic dysfunc tion [49,50] . Lamin mutations are likely the most common cause of idiopathic dilated cardiomyopathies.…”
Section: Wwwnaturecom/aps Boudoulas Kd Et Almentioning
confidence: 99%